Caribbean countries Analysis from a business perspective. An approach to a business prospectus. (2011)
This article is a synthesis of an investigation of the characteristics of themarket of the Caribbean region in relation to the cultural variables that affectthe product consumption. Such variables are of important consideration in anystrategy of the international positioning. The near future of Colombia is facinga challenge with exporting; it needs to reach the markets that have a demand ofthe Colombian’s goods and services. In conclusion, the Caribbean is a zone nearColombia that has opportunities to export, especially manufacture and services.